STUDENTS’ SPEAKING ANXIETY OF ENGLISH FOREIGN LANGUAGE (EFL) CLASS AT THE ELEVENTH GRADE OF MAN 1 BITUNG - Nur Halimah; Lies Kryati; Indah Wardaty Saud; Yulia Maulida Putri Kowaas (Universitas Muhammadiyah Gorontalo, 2020)
This research aimed to find out the level of students’ anxiety in speaking and the causes of students’ speaking anxiety in EFL class. The respondent of this research was the eleventh grade students of XI Science in MAN 1 Bitung which were consisted of 29 students. In this study, the researcher used descriptive qualitative method by using observation, questionnaire and interview to collect the data. During the implementation, the researcher utilized three steps of actions. The first action was to observe the students during their English class, the second action was to give the students questionnaire and the last action was to interview the students and the teachers. The level of anxiety was investigated through questionnaire adapted from Foreign Language Class Anxiety Scale (FLCAS). The result showed that 3% (one student) had high level of speaking English anxiety, 56% (sixteen students) had moderate level of speaking English anxiety and 41% (twelve students) had low level of speaking English anxiety. It means that most of the students experienced moderate anxiety when they speak English in class. The findings revealed that the causes of that situation including lack of English knowledge, lack of vocabulary, lack of practice, lack of confident, worried about making mistakes, worried being laughed at and afraid of being called arrogant. Therefore, it is important for the teacher to encourage and motivated the students and uses some techniques and games to help the students decrease their anxiousness.